WPC manufacturing using thermal -polyelectrolyte precipitation: A product quality and techno-economic assessment. (February 2022) - Raut, Shubhangi; Jain, Surbhi; Dhamole, Pradip; Agrawal, Shailesh
Abstract: The heat treatment followed by polyelectrolyte precipitation is evaluated as an alternate technique for membrane separation-based process for whey protein recovery. The evaluation was conducted on two parameters, quality and techno-economic analysis. The optimum conditions for maximum recovery using combined heat and polyelectrolyte carboxy methyl cellulose (CMC) were determined at lab scale. The quality of the recovered whey protein powder (WPP) was adjudged by determining the functional properties and in-vitro digestibility. The digestibility of the recovered WPP reduced with an increase in heat treatment temperature, with no impact of CMC addition on digestibility observed. The digestibility of WPP recovered at 50 °C was similar to that of commercial whey protein concentrate (CWPC). Although solubility of the recovered protein was lower, but the emulsifying properties were acceptable. For the techno-economic evaluation, a conceptual flowsheet of the thermal-polyelectrolyte precipitation plant was developed and the capital and operating cost was determined. It was found that an integrated whey processing plant producing lactose, in addition to whey protein concentrate was needed to make the project profitable. The NPV of the project came out to be 4.3 million dollars with a discounted payback period of 3.3 years. The risk analysis to quantify the probability of the project being profitable under various deviations from the base case values was done using Monte Carlo simulation. It was found that for the deviation range studied, there is a higher probability of the project being profitable. Highlights: While the yield increased, the digestibility of recovered whey protein decreased with an increase in treatment temperature. Addition of polyelectrolyte increases the protein recovery, without impacting the digestibility. An integrated lactose producing WPC plant makes the process profitable. Based on Monte Carlo simulations there exists greater probability of the project being profitable.